Instructional Variables and Students’ Acquisition of Employable Skills in Vocational Education in Nigerian Technical Colleges - Udofia, A. E; Ekpo, A. B; Nsa, S. O.; Akpan , E. O. (Mediterranean Journal of Social Sciences, 2012)
This paper focuses on teacher quality, teaching methods, and access to training materials on students’acquisition of employable skills in vocational technical subjects, for self employment in Akwa Ibom State.Three questions and three hypotheses were formulated and tested in the study. The population of the studycomprised senior technical II students in the six technical colleges in the state. The population size was 240.A random sampling technique was used to obtain a sample size of 120 students for the study. A 28 - itemstructured questionnaire titled, Students’ Acquisition of Employable Skills Questionnaire (SAESQ) with afour-point rating response options were used for data collection. Mean, Pearson Product MomentCorrelation (PPMC) and Regressional analysis were used for data analysis. The results indicated that therewas significant relationship between teacher quality and students’ acquisition of employable skills. Thefindings also revealed that there was significant relationship between teaching methods and students’ skillacquisition. This paper therefore calls for the provision of modern workshop equipment and employment ofqualified and experienced teachers for effective teaching/training of students in order to achieve theobjectives of vocational and technical education in Akwa Ibom State.